(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
In the education system, preschool children are assisted in specialized specialized kindergartens in accordance with the nature of the child’s developmental disorder. These kindergartens specialize in the education, upbringing and correction of the development of children with various disabilities, which is reflected in the relevant classifications (T. A. Vlasova, M. S. Pevsner, V. A. Lapshin, B. P. Puzanov). In preschool childhood, a base is formed for the development of speech, motor skills, all mental processes, and various types of activities.